Application of the SIP protocol in telecommunication, based on a image transmitting application - Marzec, Michal; Sakowicz, Bartosz; Mazur, Piotr; Napieralski, Andrzej (Видавництво Львівської політехніки, 2010)
This paper presents the idea of convergence of the IT and telecommunication worlds, based on an example application. The program has been developed in Microsoft Visual Web Developer 2008 environment. As one of the aims the possibilities of convergence are being described. The example application allows users to communicate by video conference using soft phone on one side and WWW browser on the other, via Internet connection.
Keywords: C#; SIP; convergence; IMS; video conferencing